Edukasi Body Image pada Remaja Putri Mahasiswa Kebidanan STIKes Muhammadiyah Ciamis - Ayu Endang Purwati; Heni Heryani; Sri Utami Asmarani; Hani Septiani; Dini Ariani (LPPM STIKes Muhammadiyah Ciamis, 2026)
Introduction: Body image refers to a person’s perceptions, thoughts, feelings, and attitudes toward the shape, size, and appearance of their body. A positive body image enhances mental health, self-confidence, and quality of life, while a negative body image increases body dissatisfaction. Adolescents are an age group undergoing rapid biological, psychological, social, and emotional changes. Negative body image among adolescents has become a public health issue worldwide, necessitating promotive and preventive interventions as a solution. Objective: The objective of this community service activity is to enhance adolescents’ knowledge, understanding, and awareness of the importance of a positive body image as a factor that supports physical and mental health. Participants were educated on the concept of body image, as well as the factors that influence their perceptions of their own bodies. Method: The literature review method was used to collect and analyze various scientific sources as a basis for developing materials, lectures, and interactive discussions, supplemented by the distribution of handouts. Pre- and post-tests were used to measure the success of the activity. Result: The event took place smoothly on August 16, 2025, at STIKes Muhammadiyah Ciamis, with 35 participants gathering on the campus grounds. Conclusion: There was an increase in knowledge regarding the importance of a positive body image through education provided during the Community Service program, as evidenced by an increase in the average pretest score from 69 to 80 on the posttest.